The Role of Strategic Transparency in Achieving Sustainable Creativity / Explanatory Study in a Group of Industrial Companies in Baghdad - majeed, Basema abood; Esmael, Sahar Khaleel (Journal of Techniques, 2021)
This research aims to identify the role of strategic transparency in achieving sustainable creativity in a group of companies in Baghdad like; the General Company for the Industry for Vegetable Oils, the National Company for Hydraulic Industries - Hydraulic Factory, the General Company for Construction Industries - Baghdad Plastic Factory. The research problem was the necessity of the companies surveyed to adopt strategic transparency to achieve sustainable innovation. The questionnaire used for data collection. It consisted of (25) paragraphs. A random sample of (67) was selected from the research community represented by workers in industrial companies. The results of data analysis by using the statistical program (SPSS V.23) showed there was a statistically significant correlation between the dimensions of strategic transparency and sustainable creativity. It also had used the Amos V.20 program to investigate the research hypotheses by path analysis. Which showed there was a significant effect of the dimensions of strategic transparency in supporting sustainable innovation. Which, supporting its applications in the industrial labor market by increasing moral and material incentives to researchers in this field.